Agile Processes in Software Engineering and Extreme Programming 24th International Conference on Agile Software Development, XP 2023, Amsterdam, The Netherlands, June 13-16, 2023, Proceedings - Stettina, Christoph J.; Garbajosa, Juan; Kruchten, Philippe (Lecture Notes in Business Information Processing, 2023)
This open access book constitutes the proceedings of the 24th International Conference on Agile Software Development, XP 2023, which took place in Amsterdam, The Netherlands, during June 13-16, 2023. XP is the premier agile software development conference combining research and practice. It is a unique forum where agile researchers, practitioners, thought leaders, coaches, and trainers get together to present and discuss their most recent innovations, research results, experiences, concerns, challenges, and trends.  XP conferences provide an informal environment to learn and trigger discussions and welcome both people new to agile and seasoned agile practitioners. This year's conference was held with the theme "Whole Team Sustainability". The 11 full papers and 1 short paper presented in this volume were carefully reviewed and selected from 40 submissions. They focus on agile practices and agile in the large.